Riometry at the Italian Antarctic station of Terra Nova Bay - De Franceschi, G.; De Santis, A.; Cerrone, M.; Chiappini, M.; Palangio, P.; Romeo, G.; Ricci, G. (Societa italiana di fisica, 1997)
A solid-state riometer has been installed at Terra Nova Bay (74-420S and 164-060E) during the IX Italian Antarctic expedition (1993/1994) to provide, in the frame of the geophysical observatories, studies on the ionospheric absorption in the lower part of the ionosphere. This kind of measurements will integrate the already existing active vertical ionospheric sounding and the magnetic absolute vector observations, with the objective of investigating the state of the ionosphere-magnetosphere coupling. In order to evaluate the base disturbance to the riometer, a remote campaign has been performed at McCarthy Ridge, rather far from the base station, where no anthropic noise is expected. Preliminary data analysis confirms the good quality of the Antarctic riometer observations.